Assessment of the Forest Remnants of Gigantes and Sicogon Islands, Iloilo province, Philippines - Bucol, Abner A. (Silliman Journal, 2022)
This paper presents the status of forest vegetation in the Gigantes and Sicogon islands, in Carles, Iloilo province, off northeastern Panay Island, Philippines. Sampling of trees was based on 27 main plots (400m2 each) while saplings and undergrowth species were sampled within 27 sub-plots (200m2) and 108 smaller sub-plots (1m2 each), respectively. A total of 88 species of forest plants CFMPOHJOHUPHFOFSBBOE’BNJMJFTIBWFCFFOJEFOUJmFEJO the 27 sampling plots. Sicogon Island has about 571.2 ha (50.29% of the total land area) of relatively intact forest while Gigante Sur and Gigante Norte have 283 ha (47.11%) and 92.73 ha (19.25%) of karst forest, respectively. The forest cover in the three islands has been altered due to farming and charcoal production. The impact of such activities may affect the fauna endemic to these small islands. Protection of the remaining forests on these islands is also recommended.